2020
DOI: 10.3389/fmicb.2020.586729
|View full text |Cite
|
Sign up to set email alerts
|

Elevating NagZ Improves Resistance to β-Lactam Antibiotics via Promoting AmpC β-Lactamase in Enterobacter cloacae

Abstract: Enterobacter cloacae complex (ECC), one of the most common opportunistic pathogens causing multiple infections in human, is resistant to β-lactam antibiotics mainly due to its highly expressed chromosomal AmpC β-lactamase. It seems that regulation of chromosomal AmpC β-lactamase is associated with peptidoglycan recycling. However, underlying mechanisms are still poorly understood. In this study, we confirmed that NagZ, a glycoside hydrolase participating in peptidoglycan recycling in Gram-negative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In the case of Pseudomonas aeruginosa , previous studies have reported a significant reduction in β-lactam resistance when peptidoglycan recycling is impeded [ 13 , 36 ]. Our earlier research findings also pointed to a noticeable decrease in β-lactam resistance in E. cloacae following NagZ deletion [ 20 ]. Nevertheless, the impact of NagZ on the virulence of E. cloacae remains unclear.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the case of Pseudomonas aeruginosa , previous studies have reported a significant reduction in β-lactam resistance when peptidoglycan recycling is impeded [ 13 , 36 ]. Our earlier research findings also pointed to a noticeable decrease in β-lactam resistance in E. cloacae following NagZ deletion [ 20 ]. Nevertheless, the impact of NagZ on the virulence of E. cloacae remains unclear.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, inhibiting NagZ has been demonstrated to decrease bacterial resistance to β-lactam antibiotics in various bacteria, including Pseudomonas aeruginosa , Stenotrophomonas maltophilia , and Yersinia enterocolitica [ 16–19 ]. Our previous research has substantiated NagZ’s critical role in regulating the expression of chromosomal AmpC β-lactamase and subsequent resistance in E. cloacae [ 20 ]. Additionally, limited studies have also reported NagZ’s involvement in bacterial biofilm synthesis and virulence regulation, such as NagZ triggers Neisseria gonorrhoeae biofilm disassembly [ 21 ] and knockout of NagZ disrupts the peptidoglycan recycling pathway, leading to reduced virulence in Pseudomonas aeruginosa [ 14 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that metabolism and recycling of peptidoglycan take part in the expression of AmpC [39,40], one of the key enzymes in peptidoglycan recycling is NagZ and its main function is to form anhMurNAc from GlcNAc-1,6-anhydroMurNAc-peptides by cleaving non reducing GlcNAc residues. 43 In the process of peptidoglycan metabolism, anhMurNAc promote the expression of AmpC by binding to the transcription factor AmpR. According to genetic research, NagZ is required for the induction of AmpC β-lactamases in Pseudomonas aeruginosa [7].…”
Section: Discussionmentioning
confidence: 99%
“…For CFZ and IMP treatment assays, the reagents were employed at the subculture stage. Western blot analysis was carried out using the standard methodology as elaborated earlier [43]. The detailed attributes of antibodies employed in western blot assay are as follows: rabbit anti-NagZ (preparation by ourselves), mouse anti-DnaK (Abcam, Cambridge, MA, USA), rabbit anti-AmpC (Abnova Taipei, Taiwan, China), goat antimouse IgG-HRP and goat anti-rabbit IgG-HRP (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA).…”
Section: The Analysis Of Protein Extraction and Western Blotmentioning
confidence: 99%
“…For CFZ and IMP treatment assays, the reagents were employed at the sub-culture stage. Western blot analysis was carried out using the standard methodology as elaborated earlier [ 36 ]. The detailed attributes of antibodies employed in western blot assay are as follows: rabbit anti-NagZ (preparation by ourselves), mouse anti-DnaK (Abcam, Cambridge, MA, USA), rabbit anti-AmpC (Abnova Taipei, Taiwan, China), goat anti-mouse IgG-HRP and goat anti-rabbit IgG-HRP (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%